The Roles of TP53 and FGFR2 in Progress Made Treating Endometrial Cancer - Olga Adamczyk-Gruszka; Agata Horecka-Lewitowicz; Agnieszka Strzelecka; Monika Wawszczak-Kasza; Jakub Gruszka; Piotr Lewitowicz (Diagnostics, 2022)
The morbidity and mortality caused by endometrial cancer (EC) is still rising worldwide. In recent years, a new system of tumor stratification has been proposed based on POLE-mutational status, TP53, and microsatellite stability status. The aim of the study was to analyze a vast panel on the genes potentially involved in the genesis of endometrial cancer in the Polish population. One hundred and three white female patients with confirmed endometrial cancer were enrolled on the study. We performed sequencing using the Hot Spot Illumina panel and microsatellite stability with immunohistochemistry. We confirmed a key role of the TP53 mutation in progress to high-grade EC and parallelly some role of FGFR2 mutation. Moreover, our data present a vast landscape of mutations in EC and their polymorphism. We reported the meaning of FGFR2 mutation and TP53 (high copy number) in high-grade ECs. Our observation in MSI contribution is comparable with other studies. Finally, we see a strong need for the implementation of the TCGA classification.